2018
DOI: 10.2106/jbjs.18.00049
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Consumption After Knee Arthroscopy

Abstract: Background: The opioid epidemic in the United States has placed increased pressure on physicians to engage in responsible opioid prescribing practices. However, surgeons currently have little information to guide their postoperative prescription decision-making. The purpose of this study was to assess opioid consumption after knee arthroscopy and identify preoperative factors that may predict higher opioid usage.Methods: A prospective observational study of 221 patients was conducted in patients undergoing out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
103
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(116 citation statements)
references
References 18 publications
(17 reference statements)
8
103
3
Order By: Relevance
“…Interestingly, although several studies have found an association between preoperative narcotic use and higher postoperative narcotic use, the current study did not find a significant difference in total opioid consumption based on preoperative opioid use. 5,7,14 An explanation for this result could be the relatively small sample size of patients with regular opioid use in the current study. A majority of patients were acutely exposed to opioids within 30 days of their surgery and only one patient chronically used opioids.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Interestingly, although several studies have found an association between preoperative narcotic use and higher postoperative narcotic use, the current study did not find a significant difference in total opioid consumption based on preoperative opioid use. 5,7,14 An explanation for this result could be the relatively small sample size of patients with regular opioid use in the current study. A majority of patients were acutely exposed to opioids within 30 days of their surgery and only one patient chronically used opioids.…”
Section: Discussionmentioning
confidence: 74%
“…[3][4][5] In a prospective observational study, Wojahn et al found that nearly half of their patients used less than 5 pills following knee arthroscopy, and over half had discontinued opioid use by postoperative day 3. 5 The study did not include knee procedures involving ligament reconstruction. When accounting for this difference in procedures, the current study 3 Additionally, the authors found a lack of patient knowledge and education regarding opioid disposal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient factors appear more important than legislative or surgical factors for predicting chronic opioid use. Multiple studies have previously evaluated risk-factors for prolonged or chronic opioid use following musculoskeletal surgery [16][17][18][19]23,34,36,39,40]. As in this study, the most commonly cited risk factor is preoperative opioid use.…”
Section: Discussionmentioning
confidence: 96%
“…Although providers previously may have overprescribed opioids for fear of inadequate postoperative pain control, it appears that a 150 MME prescription following ACDF is generally sufficient. A number of studies have found that orthopedic patients routinely receive more postoperative opioids than required to control their pain [26,27,33,34]. Such overprescribing results in unused pills and diversion of narcotics, a primary driving force behind prescription opioid abuse [28].…”
Section: Discussionmentioning
confidence: 99%